2022
DOI: 10.1002/vms3.960
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on pharmacological effects and new dosage forms of baicalin

Abstract: Background: As a kind of flavonoid, baicalin (C 21 H 18 O 11 ) is extracted from Scutellaria baicalensis Georgi, the extract of which can be added to animal feed in China. Objectives:The present review will describe the current understanding of the pharmacological effects of baicalin in the regulation of inflammation, oxidative stress anti-virus and anti-tumour responses. Methods:We highlight emerging literature that the application in livestock health and performance, the biological activities, the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 126 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Baicalin, a flavonoid extracted from Scutellaria baicalensis Georgi, exhibits diverse bioactivities including antibacterial, anti-inflammatory, anti-allergic, anticonvulsant, anticancer and anti-ultraviolet effects ( Bao et al, 2022 , Wen et al, 2023 ). Our prior investigations have shown that baicalin exhibited in vitro and in vivo efficacy against gouty arthritis ( Wen et al, 2017 , 2018), and also mitigates hyperuricemic nephropathy via inhibition of the PI3K/AKT/NF-κB signaling pathway ( Liu et al, 2023a , Liu et al, 2023b , Xiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin, a flavonoid extracted from Scutellaria baicalensis Georgi, exhibits diverse bioactivities including antibacterial, anti-inflammatory, anti-allergic, anticonvulsant, anticancer and anti-ultraviolet effects ( Bao et al, 2022 , Wen et al, 2023 ). Our prior investigations have shown that baicalin exhibited in vitro and in vivo efficacy against gouty arthritis ( Wen et al, 2017 , 2018), and also mitigates hyperuricemic nephropathy via inhibition of the PI3K/AKT/NF-κB signaling pathway ( Liu et al, 2023a , Liu et al, 2023b , Xiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…26 The main active component of Huangqin is baicalin, which has antibacterial, anti-inflammatory, antioxidant, antiviral, and anticancer properties. 27,28 Baicalin contains a large conjugated system (Fig. 1) and is easily chelated with metal ions due to its o-diphenol hydroxyl and carboxyl groups as well as carbonyl.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin (BA) (Figure 1B) is a flavonoid with significant biological activities, which is the main component of the dried root of the traditional Chinese medicine Scutellaria baicalensis Georgi [9]. Studies have found that baicalin is a multi-target, multi-channel drug with antibacterial, antiviral, antitumor, hepatoprotective, and other pharmacological effects, among which baicalin's hepatoprotective effects are the most significant [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…BA can significantly downregulate the expression of HNF 1 α and HNF 4 α in time and dose, thereby exerting anti-HBV effects [13].For duck hepatitis A virus type 1 (DHAV-1)-infected duck liver cells, BA mainly restores the mitochondrial structural integrity of duck liver cells to maintain their function, while lowering the production of ROS, thereby effectively improving the harm caused by oxidative stress to liver cells [14]. SREBP 1c is an important regulator of liver fat formation induced by alcohol and a highfat diet, and the vital way BA improves fatty liver is by reducing the formation of liver fat by inhibiting the activity of SREBP 1c and enhancing the liver's ability to decompose fat Baicalin (BA) (Figure 1B) is a flavonoid with significant biological activities, which is the main component of the dried root of the traditional Chinese medicine Scutellaria baicalensis Georgi [9]. Studies have found that baicalin is a multi-target, multi-channel drug with antibacterial, antiviral, antitumor, hepatoprotective, and other pharmacological effects, among which baicalin's hepatoprotective effects are the most significant [10][11][12].…”
Section: Introductionmentioning
confidence: 99%